Keeping up or falling behind? The impact of benefit and tax uprating on incomes and poverty - Holly Sutherland; Ruth Hancock; John Hills; Francesca Zantomio (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Each year, the Government decides how much to raise benefits and tax allowances. In the UK the basis for these upratings is rarely debated, yet has major long-term consequences for the relative living standards of different groups as well as for the public finances. This paper considers the medium term implications of present uprating policies which vary across parameters of the tax-benefit system. Continuing for 20 years, other things staying the same, would result in a near doubling of the child poverty rate alongside a substantial gain to the public finances. At the same time pensioners are largely protected by the earnings indexation of pensioner benefits and, in time, the basic state pension. We show how difficult it will be to meet the UK child poverty targets unless the greater inequality inherent in the current regime for uprating payments and allowances is redressed.
Keywords: 330